STRATEGI PENGEMBANGAN PARIWISATA BERBASIS EKONOMI KREATIF DI KOTA SURAKARTA - Hidayanti, Sofiyana; Eka Mahadewi, Ni Putu; Sudiarta, I Nyoman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p18, 2023)
This study was conducted to determine the internal and external factors of the development of tourism and the creative economy of the city of Surakarta, so that it can be seen the right strategy to develop tourism based on the creative economy. Data collection techniques in this study are observation, interviews, questionnaires, documentation and literature study. The sampling technique used was purposive sampling. Qualitative descriptive analysis, quantitative descriptive analysis, IFAS and EFAS matrix analysis, and SWOT analysis were selected in this study. The internal environment was analyzed based on 4A potentials (attractions, amenities, accessibilities, and ancilliary) while the external environment was analyzed based on PEST factors (Political, Economic, Social and Technological). The scores obtained on the IFAS and EFAS metrics are in the category of Aggressive strategy, and the short-term strategy that can be applied is the SO (Strength - Opportunity) strategy.